A dynamic model of a TCP-session at the management by a length of queue with the use of RED mechanism - Starkova, O. V. (Видавництво Львівської політехніки, 2010)
a mathematical model of TCP-session of data communication at the management by a length of queue with the use of congestion avoidance mechanism – RED (Random Early Detection) – is proposed. This model is expressed by differential equations, which represent the dynamic of information exchange between hosts.
Keywords: TCP-session; RED; Telecommunication system